S19-1: The “City, Green, Go!” Toolkit for Sustainable Sport Events (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The purpose of the “City, Green, Go!” Toolkit is to promote environmental sustainability in the grassroots sport sector and empower the potential sport event organisers with knowledge and practical tips about green sport event organisation. With the use of the Toolkit, municipalities, local sport clubs, and sport professionals should gain more awareness and learn practical tools to organise more eco-friendly events, while also using the communicational power and capacity of a certain sport event to raise awareness of participants about environmental challenges.Project Description: As an output of a 2-year-long Erasmus+ sport collaborative partnership project, five main partners and an associated municipality have developed the “City, Green, Go!” Toolkit, the Toolkit for eco-friendly grassroots sports initiatives in urban settings. This Toolkit is in-between a textbook that summarises the relevant information in the field of seven carbon footprint reduction principles, namely energy, biodiversity, catering, mobility, waste reduction, sustainable materials, water conservations, and a workbook that provides practical steps and a comprehensive checklist about the aspects that should be respected when organising an urban sport event. The partners (SandSI, IsInnova, ISCA, BSK, Sport&Citizenship) developed together the Toolkit and its checklist based on the “Checklist for climate friendly exercise programmes” by Karim Abu Omar from 2021, who, as a supporting expert, together with Krisztina Csobay, a sustainability expert from Green Zone Association, has contributed to finalise the Toolkit and the checklist which summarises all tips related to seven carbon-footprint reduction principles in an easy-to-handle sheet, as the practical essence of the project.Dissemination of the Toolkit has been incorporated into the promotion of European Week of Sport in Hungary, as this EU wide campaign focuses also on the promotion of environmental sustainability in 2025. A follow-up project, to test the usability of the Toolkit and to finetune it based on the practical experiences, is under evaluation in the current Erasmus+ call.Conclusions: While promoting physical activity and sporting opportunities, grassroots sport organisations need to respect eco-friendly organisation principles. The “City, Green, Go!” Toolkit is a proper tool to raise awareness and build capacities of the urban sport event organisers in this respect.